Pengaruh Sales Promotion, Celebrity Endorsement, dan Sosial Interaction terhadap Impulsive Buying dengan Consumer Trust sebagai Intervening pada Media Sosial TikTok Shop - Alyandro, Bryan; Sadat, Andi Muhammad; Fawaiq, Muhammad (Universitas Batanghari, 2024)
This research aims to determine the influence of sales promotions, celebrity endorsements and social interactions on impulse purchases through consumer trust in TikTok Shop users in Jabodetabek. This research uses quantitative methods by collecting data through survey methods, which are distributed via Google Form. The research sample consisted of 308 respondents and was processed using SPSS 25 and AMOS 24. The research results showed that sales promotions, celebrity endorsements, and social interactions had a positive and significant effect on consumer trust. Sales promotions, celebrity endorsements, social interactions, and consumer trust have a positive and significant effect on impulse buying. Sales promotions have a positive and significant effect on impulse buying both directly and indirectly through consumer trust as a partial intervention. Celebrity endorsement has a positive and significant effect on impulse buying both directly and indirectly through consumer trust as a partial intervention. Social interaction has a positive and significant effect on impulse buying both directly and indirectly through consumer trust as a partial intervention.